Implementasi Program Wirid Jumat dalam Menanamkan Karakter Religius Siswa SMA Negeri 1 Sitiung Kabupaten Dharmasraya - Marlia Fadila Putri; Rahmi Wiza (Pendidikan Islam Anak Usia Dini STIT Palapa Nusantara, 2022)
This study aims to determine how the planning, implementation, evaluation and supporting factor and inhibibiting factors of the implementation of the Wirid Jumat program in instilling the religious character of students in SMA Negeri 1 Sitiung. Research using qualitative methods with the type of research that is field research. Data collection techniques used are observation, interviews and documentation. the results of this study indicate that the planning of this program is carried out by discussingthe schedule for the implementation of Wirid Jumat officers by the supervisor teacher in coordination with the principal. Then the implementation is carried out every Friday morning before the learning process begins, namely at 07.15-08.15 WIB in the ceremonial field with activities such reading the Al-Quran and its translation, speeches, lectures, entertainment and reading prayers. Evaluatioon of this program is carried out when this acivity is taking place by the principal or one of the teachers will provide a review on the implementation of Wirid Jumat. The religious characters embedded in the Wirid Jumat program are: obedient to Allah, responsible, disciplined, love of knowledge, obeying the rules, tolerance, togethernesss, courage, hard work, respect for people, care for the environment. Supporting factors for this activity adequate facilities, full suport from the school, student ebthusiasm, and good cooperation. While the inhibiting factors are weather, student health conditions and student order.